Effects of choir singing experience on neural encoding of sounds in the ageing brain - Putkonen, Mikko (My University, 2021)
Several studies have shown that cognitive impairment related to ageing is reflected in changes in auditory event-related potential (ERP) responses (P1, N1) and mismatch negativity (MMN). As well, musical activity, especially a professional one, has been observed to have an effect, and it has been hypothesized that musical engagement may protect the brain from the effects of ageing. The aim of this cross-sectional study was to examine whether a long-term choir singing pursuit could be reflected on the processing of general (P1, N1) or change-related auditory encoding (MMN) in seniors over 60 years of age (N = 54). As a stimuli sinusoidal sounds were used. Deviant stimuli differed from the standard either in their frequency (pitch) or spatial location. Based on previous literature it was hypothesized that the effect of choir singing experience against possible cognitive decline would be seen as decreased P1 and increased N1 amplitudes and, strengthened MMN responses relative to controls. ANOVA analysis revealed a statistically significant interaction between the group and the ERP response for spatial deviants deviating 36° or 72° degrees from the standard tone source on P1 component of the ERP signal. Against the hypothesis, P1 response of choir singers was found to be higher compared to controls with medium effect sizes in all the studied regions of interest (frontal, central or parietal). However, otherwise the groups did not differ significantly from each other. As a conclusion, with the current study design, it was not possible to demonstrate an effect of musical pursuit in the group of choir singers compared to controls in line with the hypothesis. This could possibly be due to the fact that choir singers of the study were a rather heterogeneous group in their musical skills and instead of a profession, music was a hobby for the subjects weakening the possible effect in the group. No effects were observed when groups’ ERP responses were examined in relation to age. In a post hoc regression analysis it was found that in the group of choir singers longer choir singing experience (in years) was related to better pitch discrimination, i.e., higher MMN response for pitch deviants differing one or two tempered whole tones from the standard tone. The fit of the model was best in central ROI (region of interest). Such an association was not found with easier pitch deviants or with spatial deviants. This suggests that long-term choir singing possible has an impact on auditory pitch change-related information.

Monissa tutkimuksissa on osoitettu, että ikääntymiseen liittyvä kognitiivinen heikkeneminen heijastuu auditoristen tapahtumasidonnaisten herätepotentiaalien (ERP) P1- ja N1-vasteiden sekä poikkeavuusnegatiivisuuden (MMN) muutoksiin. Niin ikään musiikillisen aktiivisuuden, erityisesti ammattimaisen muusikin harjoittamisen, on osoitettu heijastuvan näihin vasteisiin. On esitetty hypoteeseja, että musiikilliseen toimintaan osallistuminen (esim. soittaminen, laulaminen) suojaisi aivoja ikääntymisen vaikutuksilta. Tämän poikkileikkaustutkimuksen tarkoituksena oli tutkia, voisiko pitkäaikainen kuorolauluharrastus heijastua yleisiin (P1, N1) tai muutokseen liittyviin (MMN) auditorisiin herätevasteisiin yli 60-vuotiailla henkilöillä (N = 54). Tutkimuksessa käytetyt ärsykkeet olivat sinimuotoisia ääniä. Poikkeavat ärsykkeet erosivat standardiäänistä taajuudellaan tai sijainniltaan. Perustuen aikaisempiin tutkimuksiin oletettiin, että kuorolauluharrastus suojaa henkilöitä ikääntymiseen liittyvältä kognitiiviselta heikkenemiseltä heijastuen kuoroharrastajien ryhmässä matalampina P1- ja suurempina N1-vasteina, sekä vahvistuneina MMN-vasteina kontrolliryhmään verrattuna. Tilastollisesti merkitsevä vuorovaikutus ryhmän ja ERP-vasteen välillä voitiin ANOVA-analyysissä havaita P1-vasteessa sijainniltaan 36° ja 72° standardista poikkeavien äänten kohdalla. Tutkimushypoteesin vastaisesti kuorolaulajien ryhmässä P1-vaste oli suurempi kuin kontrolliryhmässä; efektikoko oli keskikokoinen kaikilla kolmella tarkastellulla aivoalueella (frontaali-, keski- tai parietaalialue). Muuten ryhmät eivät eronneet toisistaan merkittävästi. Tutkimuksen avulla ei pystytty osoittamaan oletushypoteesin mukaista vaikutusta. Tämä voi selittyä sillä, että tutkimukseen osallistuneet kuorolaulajat olivat taidoiltaan heterogeeninen, ammattilaisten sijasta harrastajista koostuva ryhmä, mikä heikentää ryhmän mahdollista vaikutusta ammattilaisista koostuvaan ryhmään verrattuna. Mitään vaikutusta ei havaittu, kun ryhmien ERP-vasteita tutkittiin ikäryhmittäin (nuoremmat/vanhemman seniorit). Post hoc -regressio-analyysissä havaittiin, että mitä pitkäkestoisempi kuoroharrastus koehenkilöllä oli, sitä parempi oli erotuskyky standardiäänestä yhden tai kahden kokosävelaskeleen poikkeamille (suurempi MMN-vaste). Malli toimi parhaiten keskimmäisessä tutkituista aivoalueista (ROI C). Vastaavaa ei havaittu helpompien, taajuudeltaan tai sijainniltaan standardista poikkeavien äänten kohdalla. Tämä antaa viiteitä siitä, että pitkäaikainen kuorolauluharrastus voi mahdollisesti vaikuttaa auditoriseen sävelkorkeuden muutokseen liittyvän informaation prosessointiin.
Keywords: choir singing, senior adult, ERP, P1, N1, MMN, pitch, location